2019
DOI: 10.3991/ijoe.v15i05.9653
|View full text |Cite
|
Sign up to set email alerts
|

Perspective Electrical Circuit Simulation with Virtual Reality

Abstract: Focusing on electrical circuits as the topic for a STEM project, this research aims to develop virtual reality media for student learning. Using virtual reality media to perform STEM electrical circuit activities, data was collected and analyzed. The virtual reality media was then evaluated by five experts who used the Index of Item-Objective Congruence (IOC) to assess its effectiveness, where the IOC for each criteria was 0.8 or higher. Moreover, after evaluating it with the Diffusion of Innovation Theory (DO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…Research has indicated that VR technology and its applications have been intensively studied in terms of the factors that contribute to its adoption and acceptance using well-known theories and models such as the Theory of Planned Behaviour (TPB), and diffusion of innovation theory (DIT). Most studies have adopted TPB (Alzahrani et al, 2017;Kennedy-Clark, 2011), and IDT (Nuanmeesri & Poomhiran, 2019;Tiwari & Damle, 2020) separately. However, there is a lack of studies that employ both theories in investigating VR adoption by science teachers.…”
Section: Introductionmentioning
confidence: 99%
“…Research has indicated that VR technology and its applications have been intensively studied in terms of the factors that contribute to its adoption and acceptance using well-known theories and models such as the Theory of Planned Behaviour (TPB), and diffusion of innovation theory (DIT). Most studies have adopted TPB (Alzahrani et al, 2017;Kennedy-Clark, 2011), and IDT (Nuanmeesri & Poomhiran, 2019;Tiwari & Damle, 2020) separately. However, there is a lack of studies that employ both theories in investigating VR adoption by science teachers.…”
Section: Introductionmentioning
confidence: 99%
“…Students learn connecting circuits by operating these models. Circuit's voltage, current, and resistance values can be displayed in headset 8 . In 3DVRLab developed by Bowen et al, user connects experimental apparatus on virtual console.…”
Section: Related Workmentioning
confidence: 99%
“…Circuit's voltage, current, and resistance values can be displayed in headset. 8 In 3DVR-Lab developed by Bowen et al, user connects experimental apparatus on virtual console. The subsystem then intelligently detects mistakes in apparatus or connections, and gives the final score.…”
Section: Circuit Experiments With Vr Headsetsmentioning
confidence: 99%
See 2 more Smart Citations